De Stier van Potter : Voorstelling en betekenis. - De Groot, J.M.; Stegeman, Elly; Dordrechts Museum, Dordrecht (Dordrecht : Dordrechts Museum, 1988)
Potter, Paulus ; van Arkel, Hans ; Bonte, Marijke ; Boogert, Eddy ; Brands, Corrie ; van Dalen, Henk ; van Dalen, Ton ; van Dijl, Cees ; Kruyt, Barbara ; Lentink, Gerhard ; Olthof, Jeroen ; de Visser, Bea
biografie
Nederlands
De Stier van Potter : Voorstelling en betekenis, Dordrechts Museum, Dordrecht, 25 september t.m 20 november 1988
boek